Shortening Fermentation Period and Quality Improvement of Fermented Fish, Chouguiyu, by Co-inoculation of Lactococcus lactis M10 and Weissella cibaria M3 - Bao, Ruiqi; Liu, Sasa; Ji, Chaofan; Liang, Huipeng; Yang, Song; Yan, Xiaoming; Zhou, Yingqin; Lin, Xinping; Zhu, Beiwei (Frontiers in Microbiology, 2018)
Chouguiyu, a Chinese traditional fermented ﬁsh, is famous for its uniquely strong odor and desirable taste. However, traditional spontaneous fermentation often resulted in contamination and unstable quality of products. In this study, individual or conjunctive inoculation of two indigenous lactic acid bacteria (LAB), Lactococcus lactis M10 and Weissella cibaria M3, were tested for their effect on improving Chouguiyu’s quality. It was showed that inoculation would not affect the system’s pH, while increased the total bacteria count and lactic acid bacteria amounts. MALDI-TOF results revealed that L. lactis M10 and W. cibaria M3 could quickly occupied a dominant position in the ecosystem, and L. lactis M10 played an important role in the control of spoilage bacteria. TVB-N, TBARS and biogenic amines results also shown that L. lactis M10 had a positive effect on improving the product’s quality. Co-inoculation of L. lactis M10 and W. cibaria M3 could promote the formation of flavor according to the E-nose and GC-MS analysis, especially for the aroma-active and key volatile compounds. PCA plots of E-nose and hierarchical clustering analysis of GC-MS revealed that the co-inoculation sample at the fifth day (LW5) was the most similar to the natural fermentation sample at the seventh day (C7). The overall acceptance of LW5 was also the closest to that of C7 in sensory evaluation. In conclusion, mixed starter culture was shown to have a good effect on improving product quality and enhancing flavor with fermentation time shorten by 29%.